Analysis of ARHGAP4 Expression With Colorectal Cancer Clinical Characteristics and Prognosis - Fu, Ming-sheng; Pan, Shu-xian; Cai, Xun-quan; Hu, Yuan-xin; Zhang, Wei-jie; Pan, Qin-cong (Frontiers in Oncology, 2022)
Background: This study aims to analyze the correlation between ARHGAP4 in expression and the clinical characteristics of colorectal cancer(CRC), and the influence of ARHGAP4 expression on the prognosis of CRC, and to evaluate whether ARHGAP4 is a potential prognostic oncotarget for CRC Methods: ARHGAP4 was identified by the Gene Expression Omnibus(GEO) database through weighted gene co-expression network analysis(WGCNA).Use the Gene Expression Profiling Interactive Analysis(GEPIA) to perform analyze expression and prognosis of ARHGAP4 in CRC. The expression of AGRGAP4 and immune cells were analyzed by the Tumor IMmune Estimation Resource (TIMER) online database. Finally, immunohistochemistry was used to analyze the expression difference and prognosis of ARHGAP4 in colorectal cancer and adjacent normal tissues, as well as the relationship between AGRGAP4 expression and clinical features of CRC. Results: We identified 4 hub genes that are related to the prognosis and recurrence of CRC from GSE97781 data, which are ARHGAP4, HOXD11, KRT16, and TESC genes. ARHGAP4 has not been reported in colorectal cancer, ARHGAP4 positively regulates PI3K-AKT-MTOR and negatively regulates Wnt/β-catenin signaling in CRC.The high expression of ARHGAP4 in COAD indicates a poor prognosis by database analysis. In our clinical data results,ARHGAP4 is highly expressed in CRC and low expressed in normal tissues adjacent to cancer, Compared with the low expression group, the high expression group has a significantly poorer prognosis. In addition, ARHGAP4 expression is related to N,M staging and clinical staging, It was negatively correlated with lymphocyte number and albumin level, and positively correlated with carcinoembryonic antigen(CEA) level. Conclusion: ARHGAP4 is related to multiple signaling pathways such as PI3K-AKT-MTOR, Wnt/β-catenin etc. The expression of ARHGAP4 is related to N,M staging and clinical staging, lymphocyte,albumin and CEA level. The high expression of ARHGAP4 in CRC has a poor prognosis.ARHGAP4 may be a potential biomarkers for a prognosis of CRC, but its function and molecular mechanism in CRC need to be further studied.